Expansion of Lophius piscatorius distribution in Iceland : exploring the ecological and economic viability for establishing sustainable monkfish fisheries in Northwestern Iceland - Rajudeen, Rikab, 1988- (2013)
Global climate change has had profound impacts on marine ecosystems by altering physical parameters such as: ocean temperature; salinity; and hydrographic features, which largely govern species richness and distribution of fish populations. In Iceland, climate change has induced northwest expansion of monkfish (Lophius piscatorius) distribution; enhancing unintended consequences which affect fisheries management under the ITQ system. This study examined the impacts of three broadly-defined regions (Northwest region, South region, and East region) collectively and individually by its constituent ports on annual monkfish landings from 1999-2012, proportion of exclusively caught versus by-caught monkfish from 1999-2012, and trends in fishing company ownership from 2002-2012. It analyzed weaknesses in monkfish management and the ITQ system while providing amendments that resolve contemporary issues marginalizing fishing-dependent communities. The study sought to provide evidence supporting the need to establish monkfish fisheries in the northwest region of Iceland. Since 1999, the South region has accounted for 47.2% (12,134 t) of monkfish landings in Iceland, while the Northwest region has accounted for 41.3% (10,607 t) of total monkfish landings. In the same time period, 42.9% of South region landings were identified as by-catch in the lumpfish season, while only 33.1% of Northwest region landings were caught as by-catch. Since 2008, the Northwest region has demonstrated greater contribution to annual monkfish landings than the South region with a 359% increase in average annual monkfish catch per port and 357.1% increase in regional contribution to annual average monkfish catch. This study indicates tremendous growth in both overall and port landings for the Northwest region; however, fishing company ownership has remained low and stagnant. Improvements to monkfish management include resolving information gaps; application of population dynamic modeling; and gear modifications. Recommendations for the amendment ...